2018
DOI: 10.1149/2.0201803jss
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Shear and Normal Force Trends in Copper Chemical Mechanical Planarization with Different Conditioning Discs

Abstract: The effect of two different commercially-available CVD-coated diamond conditioning discs on copper CMP was investigated tribologically and kinetically with the intent of correlating pad surface micro-texture to polish performance. Data analyses were particularly focused on in-situ shear and normal force measurements taken during polishing at several pressures (P) and sliding velocities (V), including Fast Fourier Transform (FFT) analysis of the data. One of the two discs consistently resulted in greater varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…As seen in Fig. 4, a plot of directivity, 10,11 or , (defined as the ratio of measured variances in shear force to those of normal force) of all data points (regardless of ring or slurry types) vs. the pseudo-Sommerfeld number follow a common trend. It must be noted that a directivity value of unity indicates that the fluctuations in shear and normal force are identical.…”
Section: Tribological Studiesmentioning
confidence: 79%
“…As seen in Fig. 4, a plot of directivity, 10,11 or , (defined as the ratio of measured variances in shear force to those of normal force) of all data points (regardless of ring or slurry types) vs. the pseudo-Sommerfeld number follow a common trend. It must be noted that a directivity value of unity indicates that the fluctuations in shear and normal force are identical.…”
Section: Tribological Studiesmentioning
confidence: 79%
“…(15) Separately, Peckler et al found that Δ somewhat increased with P × v and found a loose correlation between Δ and copper RR. (16) Mariscal et al also found a correlation between Δ and RR, but for a tungsten CMP application. (17) Mariscal el al.…”
Section: Introductionmentioning
confidence: 94%
“…(12)(13)(14)(15)(16)(17) Previous work has focused on the vibrations that occur in various CMP processes. (12)(13)(14)(15)(16)(17)(18)(19)(20)(21) Fukuroda et al, Hetherington et al, Kojima et al and Rao et al studied vibrations in CMP and found that they could be used as an end-point detection technique for polishing different materials. (18)(19)(20)(21) However, the authors did not correlate the vibrations to RR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 Directivity itself (taken from the science of characterizing old Italian violins, which believe it or not, have many similarities to CMP tools) [45][46][47][48][49][50] is defined as the ratio of measured variances in shear force to variances of normal force at a given polishing PV condition. 44,[51][52][53][54][55] Here, the fluctuating components of shear and normal forces are the key factors and not their absolute values. In this case, the ordinate and the abscissa are independent of one another, and because we use linear scales, there are no distortions or optical illusions that would have been caused by the logarithmic scales.…”
Section: Parametersmentioning
confidence: 99%